Targeting natural antioxidant polyphenols to protect neuroinflammation and neurodegenerative diseases: a comprehensive review - Jalouli, Maroua; Rahman, Md Ataur; Biswas, Partha; Rahman, Hasanur; Harrath, Abdel Halim; Lee, In-Seon; Kang, Sojin; Choi, Jinwon; Park, Moon Nyeo; Kim, Bonglee (Frontiers in Pharmacology, 2025)
Polyphenols, naturally occurring phytonutrients found in plant-based foods, have attracted significant attention for their potential therapeutic effects in neurological diseases and neuroinflammation. These compounds possess diverse neuroprotective capabilities, including antioxidant, anti-inflammatory, and anti-amyloid properties, which contribute to mitigating the progression of neurodegenerative conditions such as Alzheimer’s Disease (AD), Parkinson’s Disease (PD), Dementia, Multiple Sclerosis (MS), Stroke, and Huntington’s Disease (HD). Polyphenols have been extensively studied for their ability to regulate inflammatory responses by modulating the activity of pro-inflammatory genes and influencing signal transduction pathways, thereby reducing neuroinflammation and neuronal death. Additionally, polyphenols have shown promise in modulating various cellular signaling pathways associated with neuronal viability, synaptic plasticity, and cognitive function. Epidemiological and clinical studies highlight the potential of polyphenol-rich diets to decrease the risk and alleviate symptoms of neurodegenerative disorders and neuroinflammation. Furthermore, polyphenols have demonstrated their therapeutic potential through the regulation of key signaling pathways such as Akt, Nrf2, STAT, and MAPK, which play critical roles in neuroprotection and the body’s immune response. This review emphasizes the growing body of evidence supporting the therapeutic potential of polyphenols in combating neurodegeneration and neuroinflammation, as well as enhancing brain health. Despite the substantial evidence and promising hypotheses, further research and clinical investigations are necessary to fully understand the role of polyphenols and establish them as advanced therapeutic targets for age-related neurodegenerative diseases and neuroinflammatory conditions.